The incidence, risk factors, and clinical manifestations of hyponatremia in marathon runners - Hew, T. D.; Chorley, J. N.; Cianca, J. C.; Divine, J. G. (Clinical Journal of Sport Medicine, 2003)
Objective: To report on the incidence, identify the risk factors, and clarify the clinical manifestations of acute hyponatremia in marathon runners. Design: An observational and retrospective case-controlled series. Setting: The medical care area of the 2000 Houston Marathon. Patients: Marathon finishers treated in medical area receiving intravenous fluids (N=55), including a more detailed analysis of 39 runners completing a retrospective questionnaire. Main Outcome Measures: Vital signs, serum electrolytes, and finish time were analyzed via ANOVA studies between all non-hyponatremic (NH: N=34)) and hyponatremic (H: N=21)) runners. Fluid intake, training variables, NSAID use, and Symptomatology were further analyzed to delineate all significant differences between groups. Results: There were no significant differences in vital signs, training variables, or NSAID use between H and NH groups, although there was a trend towards the less experienced runners presenting with lower post-race sodium levels. H runners had lower potassium [K] (p=.04), chloride [Cl] (p<.001), and blood urea nitrogen [BUN] (p=.004) levels than NH runners. There was a significant inverse linear relationship between both finish time versus [Na] (r2 =.51) and total amount of fluid ingested versus [Na] (r2=.39). The total cups of water (p=.004), electrolyte/carbohydrate solution (p=.005) and total amount of fluid ingested (p<.001) were significantly higher in H compared to NH runners and the degree of hyponatremia was related in a dose dependant manner. Vomiting was observed more frequently in H than NH runners (p=.03). Conclusion: 21 runners presented to the medical area of the Houston Marathon with hyponatremia (.31% of entrants). Excessive fluid consumption and longer finishing times were the primary risk factors for developing this condition. Vomiting was the only clinical sign differentiating hyponatremia from other conditions that induce exercise-associated collapse.